Maritime Circulation of the South China Sea: A Numerical Study - Camerlengo, Alejandro Livio; Demmler, Monica Ines (Universiti Putra Malaysia Press, 1996)
A numerical model employing the classic hydrodynamic equations of conservation of mass and momentum, vertically integrated, has been developed. The model solves the external, or barotropic, mode. The computational mode is eliminated by employing a Euler backward scheme at every N (odd) time level. A similar model is used for issuing flood warnings of hurricanes and extra tropical storms. This type of model is also used in a variety of situations such as oil spill simulations, storm surges, tsunamis, and tidal simulations. The aim of this investigation is to gain some insight into the circulation of the South China Sea during the NE and SW monsoon seasons. Thus the circulation of the Malaysian EEZ has been simulated. Our results compare well with Wyrtki's (1961) observations.